Causes and Operating consequences of Corporate Cash holdings: An Empirical Study of Chinese Listed Companies - Zuo, Chen (2017)
This dissertation examines the causes and consequences of cash holdings based the sample of Chinese non-financial listed companies over the period of 2010 to 2016. The Pooled OLS model, fixed effect model, random effect model and general method of moments (GMM) applied in this study. The final results is mostly consistent with previous study, which reveals that the leverage, firm size and dividend are negatively related to corporate cash holdings while the management shareholding, the proportion of the largest shareholding, the proportion of state-owned shares and GDP growth rate are negatively correlated with corporate cash holdings. On the other hand, the impacts of cash holding on operating performance are also examined. We can conclude the companies with higher level of cash holding can gain better operating performance. The robustness test is applied to ensure the empirical result is validity and GMM is applied to supplemental analyse the dynamic relationship between cash holding and operating performance.